Antioxidant and Vitamin D supplements for athletes: Sense or nonsense? - Powers, S.; Nelson, B.; Larson-Meyer, E. (Journal of Sports Sciences, 2011)
The idea that dietary supplements can improve athletic performance is popular among athletes. The use of antioxidant supplements is widespread among endurance athletes because of evidence that free radicals contribute to muscle fatigue during prolonged exercise. Furthermore, interest in vitamin D supplementation is increasing in response to studies indicating that vitamin D deficiency exists in athletic populations. This review explores the rationale for supplementation with both antioxidants and vitamin D and discusses the evidence to support and deny the benefits of these dietary supplements. The issue of whether athletes should use antioxidant supplements remains highly controversial. Nonetheless, at present there is limited scientific evidence to recommend antioxidant supplements to athletes or other physically active individuals. Therefore, athletes should consult with their health care professional and/or nutritionist when considering antioxidant supplementation. The issue of whether athletes should supplement with vitamin D is also controversial. While arguments for and against vitamin D supplementation exist, additional research is required to determine whether vitamin D supplementation is beneficial to athletes. Nevertheless, based upon the growing evidence that many athletic populations are vitamin D deficient or insufficient, it is recommended that athletes monitor their serum vitamin D concentration and consult with their health care professional and/or nutritionist to determine if they would derive health benefits from vitamin D supplementation.